Pengertian Ilmu Akhlak Tasawuf dan Perannya dalam Menumbuhkan Karakter Mahasiswa - Nawawi, Taosyekh; Soleh, Nur; Madinah, Fikrotunisa Al; Ajmain, Maftuh (TSAQOFAH, 2025)
Morals and Sufism have an important role in shaping human personality, especially for students as the next generation of the nation. This is important because by having good morals, various other things will follow as well. Morals in Islam are not only related to behavior, but also reflect the spiritual relationship between the individual and his God. Meanwhile, Sufism as a spiritual practice aims to achieve self-purity and get closer to Allah. This study reviews the relationship between morals and Sufism, including linguistic approaches and terminology, as well as its benefits in human life. In historical development, Sufism has developed through various schools and figures who contributed to the spread of spiritual values ​​in society, including in Indonesia. The positive impacts of Sufism include the formation of an attitude of sincerity, inner peace, and piety, while the negative impacts can be a tendency to isolate oneself in an extreme way. This study confirms that morals and Sufism are interrelated in shaping humans who have noble morals and are oriented towards spiritual values.